Vasculoprotective Effects of 3-Hydroxybenzaldehyde against VSMCs Proliferation and ECs Inflammation - Kong, Byung Soo; Im, Soo Jung; Lee, Yang Jong; Cho, Yoon Hee; Do, Yu Ri; Byun, Jung Woo; Ku, Cheol Ryong; Lee, Eun Jig (PLOS ONE, 2016)
3-hydroxybenzaldehyde (3-HBA) is a precursor compound for phenolic compounds like Protocatechuic aldehyde (PCA). From recent reports, PCA has shown vasculoprotective potency, but the effects of 3-HBA remain unclear. The aim of this study is to investigate the vasculoprotective effects of 3-HBA in endothelial cells, vascular smooth muscle cells and various animal models. We tested effects of 3-HBA in both vitro and vivo. 3-HBA showed that it prevents PDGF-induced vascular smooth muscle cells (VSMCs) migration and proliferation from MTS, BrdU assays and inhibition of AKT phosphorylation. It arrested S and G0/G1 phase of VSMC cell cycle in PI staining and it also showed inhibited expression levels of Rb1 and CD1. In human umbilical vein endothelial cells (HUVECs), 3-HBA inhibited inflammatory markers and signaling molecules (VCAM-1, ICAM-1, p-NF-κB and p-p38). For ex vivo, 3-HBA has shown dramatic effects in suppressing the sprouting from aortic ring of Spargue Dawley (SD) rats. In vivo data supported the vasculoprotective effects of 3-HBA as it inhibited angiogenesis from Matrigel Plug assay in C57BL6 mouse, prevented ADP-induced thrombus generation, increased blood circulation after formation of thrombus, and attenuated neointima formation induced by common carotid artery balloon injury of SD rats. 3-HBA, a novel therapeutic agent, has shown vasculoprotective potency in both in vitro and in vivo.